2019
DOI: 10.1021/acsomega.8b03277
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Viral Detection Platform Based on a Aptamers-Integrated Microfluidic Channel

Abstract: A polydimethylsiloxane-based microfluidic device has been developed for the multiplex detection of viral envelope proteins such as Zika and chikungunya on a single platform using aptamer–analyte interactions. The channel is integrated with microsized pillars that increase the surface area allowing more aptamers to attach to the incoming envelope protein molecules, thus increasing the overall sensitivity of the system. The working of the device depends on the formation of protein-mediated sandwich morphology th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…36 Because the Zika virion is similar in size to AuNPs, 24 the AuNPs may not be approaching the minimum distance needed for interparticle plasmon-plasmon interactions to ensue. Speaking to the spec-icity of the Apt-AuNP system, previous work in our lab has shown that ZIKV-E aptamers and aptamers generated against chikungunya envelope protein 1 (CHIKV-E1) show no cross reactivity in a microuidic-based assay 37 and, as stated in the Experimental section, our ZIKV-E binding aptamer was negatively selected against recombinant dengue envelope protein during SELEX. This shows that we can distinguish between avivirus and alphavirus envelope proteins though future work will incorporate live aviviruses like dengue or West Nile to see if this assay can distinguish whole virions of related viruses.…”
Section: Discussionmentioning
confidence: 99%
“…36 Because the Zika virion is similar in size to AuNPs, 24 the AuNPs may not be approaching the minimum distance needed for interparticle plasmon-plasmon interactions to ensue. Speaking to the spec-icity of the Apt-AuNP system, previous work in our lab has shown that ZIKV-E aptamers and aptamers generated against chikungunya envelope protein 1 (CHIKV-E1) show no cross reactivity in a microuidic-based assay 37 and, as stated in the Experimental section, our ZIKV-E binding aptamer was negatively selected against recombinant dengue envelope protein during SELEX. This shows that we can distinguish between avivirus and alphavirus envelope proteins though future work will incorporate live aviviruses like dengue or West Nile to see if this assay can distinguish whole virions of related viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Aptamers with high selectivity towards viruses were attached to the micro-sized pillars of a microfluidic channel. The detection took place inside the microfluidic channel and the pillars aided in enhancing the surface of the sensing area [ 66 ]. The device works with the interaction of a protein-mediated sandwich with an aptamer-AuNP conjugate.…”
Section: Aptamers In Infectious Disease Diagnosismentioning
confidence: 99%
“…In this way, colorimetric aptasensor can precisely diagnose the chikungunya and Zika envelope proteins in calf blood samples (100 pM) and phosphate-buffered saline (1 pM). The schematic of the detailed colorimetric multiplex aptasensor is represented in Figure 1 [ 66 ].…”
Section: Aptamers In Infectious Disease Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 These receptors called aptamers (a term with Latin and Greek origins: aptus meaning t and meros meaning part) have shown notable moldable selectivity for diverse target analytes, ranging from small inorganic molecules, ions, sugars, proteins, and viruses to cells. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Such a varied target range is lacking in antibody generation due to the restriction of target receptor exposure in their native forms. This is more evident in whole cells where the surface antigens contain certain hidden trans-membrane regions, a fact which is generally not accounted for during the maturation of antibodies.…”
Section: Introductionmentioning
confidence: 99%